(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social media is mostly being utilised more and more as a vital information source, especially during recent global crises like the Covid 19 epidemic. The proliferation of information gleaned from social media exposes individuals to risks to their mental well-being. The current study looks at the relationship between using social media and mental health, with a particular emphasis on the consequences of the pandemic on social media users’ emotional well-being. According to the findings, social media users’ emotional tension, rage, and anxiety would rise in response to an increase in false information, hate speech, and unconfirmed news.